BSA adsorption onto commercial activated carbon modified by microwave assisted chemical activation - Taskin, M. B.; Ozbek, S.; Demirhan, E.; Ozbek, B. (BULGARIAN ACAD SCIENCE, 2016)
In the study, effects of pH and temperature on the equilibrium and the kinetics of bovine serum albumin (BSA) adsorption onto commercial and modified activated carbon were investigated. Activated carbon was modified firstly by treatment with Na2CO3, secondly thermally treated by microwave technique, and finally subjected to treatment with HCl. The modified activated carbon samples were characterized by Fourier Transform Infrared (FTIR) and BET analyses. The results indicated that it was possible to increase the surface area of the commercial activated carbon (CAC) after the modification process (MAC) with an enhancement percentage of 59%, compared to initial untreated CAC sample. The adsorption capacities decreased at pH values lower and higher than the isoelectric point value; and increased with increasing temperature for both activated carbon samples. Moreover, adsorption isotherm and kinetic data were well explained by the Langmuir isotherm and pseudo-second order kinetic models, respectively.
Keywords: Bovine serum albumin; activated carbon; microwave treatment; modification; adsorption; isotherm models; kinetics; BOVINE SERUM-ALBUMIN; PROTEIN; SPECTROSCOPY; PROPERTY; PH; Chemistry